Rancangan Perbaikan Kualitas Produk Kerupuk Di CV Cemara - Chandrahadinata, Dody; herlina, Lina (Institut Teknologi Garut, 2025)
Product quality is one of the main factors that determine the success of a company in meeting customer needs. The main problem found at CV Cemara is the number of defective cracker products with broken and moldy conditions. This study aims to find a quality improvement design to overcome CV. Cemara in the cracker products produced. The data processing method is using Six Sigma with the DMAIC stage with the result of reducing the defect of broken cracker products reduced by 38% or to 11 kg / day. The results of the analysis show that the implementation of the DMAIC cycle and the validation of improvements in making Product Operational Standards (SOPs) in increasing the company's Sigma level, from 2.74 to sigma level 3. This shows that the improvement in making SOPs has successfully overcome the main problems of CV. Cemara.